FEMINISME DAN ISLAM - Saidul Amin (Universitas Islam Negeri Imam Bonjol Padang, 2013)
This article would like to elucidate the history and the difference betwen the movement of feminism in west and Islam and the status of woman in Islam. According to western perspective feminism is a history of struggles for women’s rights and freedoms and emphasizes that religion is one of the chief enemies of its progress. Unfortunately, many of the goals of western feminism are not necessarily relevant across cultural boundaries. On other hand, Islam gives a special rights, freedoms and place to women. So, what is the concept of the feminism is still viable adopted in the Islamic world ?Keywords : Feminism, Islam, west, movement, rights, freedomsCopyright © 2013 by Kafa`ah All right reservedDOI: 10.15548/jk.v3i2.38